Relating brain structure images to personality characteristics using 3D convolution neural network. Issue 3 (3rd March 2021) - Cao, Lixian; Liang, Yanchun; Lv, Wei; Park, Kaechang; Miura, Yasuhiro; Shinomiya, Yuki; Yoshida, Shinichi
Abstract: The Keras deep learning framework is employed to study MRI brain data in a preliminary analysis of brain structure using a convolutional neural network. The results obtained are matched with the content of personality questionnaires. The Big Five personality traits provide easy differentiation for dividing personalities into different groups. Until now, the highest accuracy obtained from the results of personality prediction from the analysis of brain structure is about 70%. Although there is still no effective evidence to prove a clear relationship between brain structure and personality, the obtained results could prove helpful in understanding the basic relationship between brain structure and personality characteristics.